Analysis of the Vegetative Growth Development and Phenology of Hop Cultivars Grown in the Subtropics Under a Two-Crop-a-Year System - Nathalia Rodrigues Leles; Alessandro Jefferson Sato; Robson Fernando Missio; Laura Baiocco Araldi; Aline Cristina de Aguiar; Sergio Ruffo Roberto (Horticulturae)
The aim of this study was to characterize the vegetative growth development of hop plants grown in the subtropics under a two-crop-a-year system with artificial supplementation lighting. The development of ‘Mapuche’ and ‘Spalter’ hops was compared during the summer 2022–2023, fall 2023, summer 2023–2024 and fall 2024 harvest seasons, considering the effects of the air temperature on the vegetative growth of plants from thermal sums in a subtropical climate region. The experiment was conducted in Palotina, Paraná, Brazil (24°17′40.05″ S, 55°50′23.16″ W, at 332 m elevation). The hops were trained on a 5.5 m high vertical trellis, using a ‘V’-shaped training system. Vegetative growth was evaluated based on the plant height development (m), hop growth rate (HGR), and classification of four growth stages based on the HGR. The phenology of the hop cultivars was determined visually according to the duration in days of the phenological stages. The development of the plant height and HGR was analyzed by nonlinear regressions of the Gompertz model and Gaussian function, respectively. ‘Mapuche’ and ‘Spalter’ hops had complete vegetative growth and phenological phases in the summer and fall seasons, with greater precocity in plant development in the summer season. The growth model based on the air temperature demonstrated that under subtropical conditions, the growth was maximized in seasons with higher temperatures. The duration of the phenological phases and the complete cycle of the plants was influenced by the vegetative growth of each cultivar in each harvest season. Therefore, double annual crop production of the hop cultivars ‘Mapuche’ and ‘Spalter’ is possible in a subtropical climate with artificial light supplementation.